1996
DOI: 10.1128/mcb.16.8.4512
|View full text |Cite
|
Sign up to set email alerts
|

An 18-Base-Pair Sequence in the Mouse Proα1(II) Collagen Gene Is Sufficient for Expression in Cartilage and Binds Nuclear Proteins That Are Selectively Expressed in Chondrocytes

Abstract: The molecular mechanisms by which mesenchymal cells differentiate into chondrocytes are still poorly understood. We have used the gene for a chondrocyte marker, the pro␣1(II) collagen gene (Col2a1), as a model to delineate a minimal sequence needed for chondrocyte expression and identify chondrocyte-specific proteins binding to this sequence. We previously localized a cartilage-specific enhancer to 156 bp of the mouse Col2a1 intron 1. We show here that four copies of a 48-bp subsegment strongly increased promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(164 citation statements)
references
References 24 publications
7
156
1
Order By: Relevance
“…5DЈ,FЈ). As the Col2a1 promoter and enhancer are directly activated by Sox9, which is expressed in differentiating chondrogenic mesenchymal condensations (Wright et al 1995;Lefebvre et al 1996), our results indicate that Wnt14 signals though ␤-catenin in differentiating chondrocytes in vivo to reverse chondrocyte differentiation, the first step in synovial joint formation.…”
Section: Ectopic Expression Of a Constitutively Active ␤-Catenin Or Wmentioning
confidence: 64%
“…5DЈ,FЈ). As the Col2a1 promoter and enhancer are directly activated by Sox9, which is expressed in differentiating chondrogenic mesenchymal condensations (Wright et al 1995;Lefebvre et al 1996), our results indicate that Wnt14 signals though ␤-catenin in differentiating chondrocytes in vivo to reverse chondrocyte differentiation, the first step in synovial joint formation.…”
Section: Ectopic Expression Of a Constitutively Active ␤-Catenin Or Wmentioning
confidence: 64%
“…The cDNA encoding human SOX9 was cloned into the pGL3-control plasmid (Promega) to replace the luciferase gene. The 4 ϫ 48-p89 luciferase construct and its MA6 mutant were described previously (44,45). For some experiments, cells were incubated with 10 M of one of the p38 inhibitors, SB202190, SB203580, and SB220025 or the inhibitor of MAPK-activated protein kinase 2 (Calbiochem) for the last 12 h. Cell culture and transient transfections were described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Sp1 binding sites in the proximal promoter are believed to be important for efficient enhancer-mediated transcription (17) and Sp1 binding activity differs between differentiated and dedifferentiated chondrocytes (18). Although it has been reported that a fragment from the first intron enhancer can direct chondrocyte-specific expression through a heterologous promoter (12), it is likely that in vivo, the endogenous Col2a1 promoter also participates in gene regulation during certain developmental stages and in response to specific regulatory signals. In fact it has been reported recently that both positive and negative elements are located in the 5Ј-flanking region of the human COL2A1 gene and participate in developmental stage-and tissue-specific expression in transgenic mice (19).…”
mentioning
confidence: 99%
“…Previously, an enhancer element was discovered in the first intron of the rat gene that was required for chondrocyte-specific expression in vitro (10,11). Other recent studies have identified additional cis-acting regulatory sequences in the first intron of the gene and identified specific transcription factors involved in regulating Col2a1 transcription (12)(13)(14)(15). However, relatively little work has been reported on characterizing cis-acting DNA elements or regulatory proteins operating in the 5Ј-flanking region of the gene.…”
mentioning
confidence: 99%